2016
DOI: 10.1073/pnas.1603325113
|View full text |Cite
|
Sign up to set email alerts
|

CD8 T cell-mediated killing of orexinergic neurons induces a narcolepsy-like phenotype in mice

Abstract: Narcolepsy with cataplexy is a rare and severe sleep disorder caused by the destruction of orexinergic neurons in the lateral hypothalamus. The genetic and environmental factors associated with narcolepsy, together with serologic data, collectively point to an autoimmune origin. The current animal models of narcolepsy, based on either disruption of the orexinergic neurotransmission or neurons, do not allow study of the potential autoimmune etiology. Here, we sought to generate a mouse model that allows deciphe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
87
1
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 120 publications
(93 citation statements)
references
References 49 publications
4
87
1
1
Order By: Relevance
“…Somatic upregulation of MHC I on neurons may also mark these cells for elimination by anti‐neuronal T cells, leading to loss of neurons in otherwise normal appearing gray matter. Indeed several studies have shown that targeting neoantigens to CNS neuronal subsets results in rapid clearance by antigen‐specific CD8 + T cells 15, 69, 70, 71. Finally, anterograde transport of MHC class I molecules into the distal axon makes these molecules available near the site of inflammation, where they may increase vulnerability to attack by autoreactive anti‐axonal CD8 + T cells 10.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Somatic upregulation of MHC I on neurons may also mark these cells for elimination by anti‐neuronal T cells, leading to loss of neurons in otherwise normal appearing gray matter. Indeed several studies have shown that targeting neoantigens to CNS neuronal subsets results in rapid clearance by antigen‐specific CD8 + T cells 15, 69, 70, 71. Finally, anterograde transport of MHC class I molecules into the distal axon makes these molecules available near the site of inflammation, where they may increase vulnerability to attack by autoreactive anti‐axonal CD8 + T cells 10.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed several studies have shown that targeting neoantigens to CNS neuronal subsets results in rapid clearance by antigen-specific CD8 + T cells. 15,[69][70][71] Finally, anterograde transport of MHC class I molecules into the distal axon makes these molecules available near the site of inflammation, where they may increase vulnerability to attack by autoreactive anti-axonal CD8 + T cells. 10 As discussed below, these findings have significance for the study of neurological conditions in which axonal injury processes may contribute to clinical progression.…”
Section: Discussionmentioning
confidence: 99%
“…Extending on prior work 1-6 a large recent GWAS analysis in over 4,500 patients across multiple ethnic groups confirmed primordial importance of the Human Leukocyte Antigen (HLA) DQ0602 heterodimer in disease predisposition, with important secondary associations in T cell receptor loci and and other loci suggesting importance of DQ0602 presentation of antigens to CD4 + by Antigen Presenting Cells (APC) and likely subsequent CD8 + destruction of hypocretin cells 29 . Hypocretin cell killing through CD4 + and CD8 + mediation has also been shown to cause narcolepsy in an animal model 30 .…”
Section: Main Textmentioning
confidence: 99%
“…Since it is very difficult to induce a CD8 + T‐cell mediated autoimmune response directly by active sensitization, such models are either induced by coupling a brain antigen with a virus vaccine (Ji et al, ) or by using a transgenic approach. In the latter, a foreign protein is expressed in transgenic animals in different cells of the central nervous system, such as astrocytes (Cabarrocas et al, ), oligodendrocytes (Na et al, ; Saxena et al, ), or neurons (Bernard‐Valnet et al, ). Disease is then transferred by the systemic injection of specific CD8 + T‐cell lines into the transgenic recipient animals.…”
Section: The Spectrum Of Inflammatory Diseases Of the Brain And Spinamentioning
confidence: 99%